Exploring culturally competent telepractice in early communication intervention : cultural considerations in working with parent-child pairs in Malaysia : a thesis presented in partial fulfilment of the requirements for the degree of Master of Speech Language Therapy, Massey University, Albany, New Zealand - Hoh, Esther (Massey University, 2018)
Current recommendations within the field of early communication intervention (ECI) includes a family-centred approach, the establishment of a collaborative relationship and using naturalistic learning opportunities as a context for intervention delivery. These suggestions have led to the development of a triadic intervention relationship which involves the family-speech-language therapist (SLT) and family-child relationship. However, the practical application of these recommendations in both contexts of the intervention relationship need to be guided by the families' cultural values. The cultural construct of individualism-collectivism has been recommended as a way of understanding the relationship between the individual's cultural value patterns and how this might be displayed in their communication behaviours. The mode of telepractice was used in this exploration of delivering ECI cross-culturally as it enabled the investigation of the triadic relationship and provided access to a culturally different context. Despite the capacity of telepractice to provide services across cultures, no studies have been published on its delivery of ECI cross-culturally. A practitioner inquiry design was chosen to explore the implementation and investigation of my personal practice in delivering ECI while adjusting it to meet the families’ cultural needs. An adapted version of the Internet-based Parent-implemented Communication Strategies (iPiCS) programme was delivered to 2 parent-child pairs from Malaysia, a nation that has been identified to exhibit cultural value patterns that align with collectivism. The qualitative data collection methods were also used to support ongoing planning and implementation of ECI. This included ethnographic interviews, field notes, parent-child observations and self-reflections which were analysed using an inductive and a deductive approach. The key findings that emerged were the themes (1) Engagement and Collaborative Strategies, (2) Experience of Early Intervention (EI), (3) Parenting Values, and (4) Perception of Support. These themes were discussed and presented as a Cultural Practice Model for SLTs to use when delivering cross-cultural ECI.
Keywords: Speech therapy for children -- Malaysia; Communicative disorders in children -- Treatment -- Malaysia; Telecommunication in medicine -- Cross-cultural studies; Parent and child -- Malaysia; Malaysia -- Social life and customs